A simple solution combustion method for the synthesis of V2O5 nanostructures for supercapacitor applications - Sutrave, Shivani (2023)
The enhanced power density, long term cycling stability, and fast rate of operation, makes supercapacitors as desirable energy storage devices. Though metal oxides play a significant part in energy storage systems, Vanadium oxides have piqued the interest of electrochemists due to their multi-valency, potential window, unique layer structure, affordability, and plentiful availability. Vanadium pentoxide typically has relatively low specific capacitance due to its weak electrical conductivity and ionic diffusivity. However, these properties can be enhanced by encasing vanadium pentoxide in metal or carbonaceous materials, reducing it to the nanoscale, or changing its shape. On the other hand, the synthetic strategies are mostly essential in raising a compound's specific capacitance. Here, we report the synthesis of vanadium pentoxide nanoparticles using a cost effective solution combustion method. The synthesized material was characterized by X-ray diffraction analysis, UV-Vis Spectroscopy, FT-IR Spectroscopy, Scanning Electron Microscopy, Cyclic voltammetry, Galvanostatic Charge-discharge, and Electrochemical Impedance Spectroscopy. The crystallite size of obtained nanoparticles is 28 nm. The specific capacitance of Vanadium pentoxide nanoparticles is 310 F/g and is calculated at 1 A/g using Galvanostatic Charge-discharge method. The obtained specific capacitance is higher than the existing reports on V2O5 nanoparticles.